GEOCHEMISTRY AND GEOLOGICAL STRUCTURE CONTROL STUDY OF PULOSARI THERMAL MANIFESTATION AREA, DIENG GEOTHERMAL FIELD, CENTRAL JAVA - Saepul Fahmi, Asep
Dieng Geothermal Field is a volcanic geothermal system located in the Dieng plateau at elevation of over 2000 meters. The Dieng geothermal resource is associated with the Quaternary andesitic volcanic mountain range. This geothermal system is known to have two reservoirs, i.e. Sikidang and Sileri reservoirs. The Sikidang reservoir is associated with Mt. Pangonan and the Sileri reservoir is associated with Mt. Merdada. Pulosari thermal manifestation area, which is the object of this research, is situated 3 km to the southwest of the Sileri reservoir, i.e. at the foot of Mt. Bisma. In the Pulosari area, there are hot springs with temperatures ranging between 50 and 67°C. The purpose of this study is to understand the geological and geochemical models of the Pulosari thermal manifestation area. The objectives of this study are to determine the geological structures controlling the existence of the manifestation in the Pulosari area, characteristics of hydrothermal fluids, as well as the fluid flow patterns and processes occurring in subsurface. The methods carried out are literature study, geological structure mapping in the manifestation area, and geochemical analysis of the manifestation water. The geochemical analysis of water includes analysis of anions, cations, and stable isotopes of ? 2H and ? 18O. The result indicates that the controlling factor of the existence of thermal manifestations in the Pulosari area is the Sikunang fault. The fault is a west-east trending normal fault forming as a result of stresses brought by volcanic activity. The water types of the Pulosari manifestations are immatures Cl-HCO3 waters. Meteoric water infiltrates and is heated by the magmatism remnants from Mt. Bisma before discharged in the upflow zone through the Sikunang fault. As the deep geothermal fluid discharges to the surface and it undergoes boiling then mixing with meteoric water, and water-rock interaction. The Pulosari reservoir hostrock is Lava and Tuff Breccia Prau and is at ±400 meters depth. The Pulosari reservoir temperature, based on the conductive-quartz geothermometer, is 180±10°C.